Many Rivers to Cross - Zigal, Thomas (Book collections on Project MUSE., 2013)
Hurricane Katrina struck the Louisiana Gulf Coast in late August of 2005. In the aftermath of the category-three hurricane, the churning waters of Lake Pontchartrain tore through the levee system of New Orleans, causing unprecedented flooding and stranding those who had failed to evacuate in time. Images of desperate men and women clinging to rooftops and praying for rescue filled every news station. It is in this setting that Thomas Zigal's new novel unfolds.